Bottom-up effect of nitrogen fertilization on the density of the corn leafhopper and its impact on both disease incidence and natural parasitism - Virla, Eduardo Gabriel; Luft Albarracín, Erica B.; Díaz, Cecilia; Van Nieuwenhove, Guido Alejandro; Fernandez, Franco Daniel; Coll Aráoz, María Victoria; Melchert, Nicolás A.; Conci, Luis Rogelio; Gimenez, Maria De La Paz (Springer, 2022)
The corn leafhopper Dalbulus maidis is a specialist herbivore that attacks maize in the tropical and subtropical regions of the Americas. It is the vector of three relevant plant pathogens that are responsible for severe yield losses. Modern agriculture is dependent on the addition of fertilizers, especially nitrogen, which may influence the nutritional quality and/or the defense ability of the plants possibly with a subsequent increment of herbivorous insect populations. Through a field experiment, using a randomized design with four treatments with incremental levels of fertilization, we evaluated the effects of nitrogen in corn on the population level of the vector D. maidis, on the incidence of the diseases transmitted by it, and on the level of parasitism of the vectors’ eggs. The amount of nitrogen fertilizer used significantly influenced the density of the corn leafhopper and, as a consequence, the parasitism by egg parasitoids, but not the incidence of the diseases transmitted by it. Two weeks after fertilization, the vector density was significantly higher in the highly fertilized treatment. The disease incidence was not directly linked with the level of fertilization. However, the symptoms of the diseases were much less evident in plants that received higher fertilization. Levels of parasitism by egg parasitoids increased accordingly to the level of D. maidis populations. The management of nitrogen fertilization in corn crops can mitigate the negative effects of the corn stunting disease without affecting the levels of natural control performed by egg parasitoids.